Pemberdayaan Santri melalui Program “Clean Area” di Pondok Pesantren Sunan Drajat Paciran Lamongan - Abdul Mun’im; Moh. Khaeruddin; Desfri Maulana Amkas; A. Khairuddin (Santri: Journal of Student Engagement, 2023)
Sunan Drajat Islamic Boarding School is a boarding school located in Banjarwati village, Paciran sub-district which is located in a large complex and is currently in the process of moving towards a clean environment. The Sunan Drajat Islamic Boarding School will later become an example for other pesantren, especially those in Lamongan and East Java in an effort to improve the quality of a clean environment. The obstacles faced are the lack of motivation and awareness of the students about the culture of clean living. So the solution that can be given is to hold a socialization of the "Clean Area" movement by means of community service with students and the management of the Sunan Drajat Islamic Boarding School. The purpose of this program is to empower the students of the Sunan Drajat Islamic Boarding School in instilling awareness and concern as well as direct involvement in the program. Then the method used is to collect data and observe directly in the surrounding environment by paying attention to the daily behavior of students and also paying attention to the amount of waste that is transported every day.